A study of the water molecule using frequency control over nuclear dynamics in resonant X-ray scattering. Issue 30 (29th March 2017) - Vaz da Cruz, Vinícius; Ertan, Emelie; Couto, Rafael C.; Eckert, Sebastian; Fondell, Mattis; Dantz, Marcus; Kennedy, Brian; Schmitt, Thorsten; Pietzsch, Annette; Guimarães, Freddy F.; Ågren, Hans; Gel'mukhanov, Faris; et al.
Abstract : We report a full analysis of the resonant inelastic X-ray scattering spectra of H2 O, D2 O and HDO. Abstract : In this combined theoretical and experimental study we report a full analysis of the resonant inelastic X-ray scattering (RIXS) spectra of H2 O, D2 O and HDO. We demonstrate that electronically-elastic RIXS has an inherent capability to map the potential energy surface and to perform vibrational analysis of the electronic ground state in multimode systems. We show that the control and selection of vibrational excitation can be performed by tuning the X-ray frequency across core-excited molecular bands and that this is clearly reflected in the RIXS spectra. Using high level ab initio electronic structure and quantum nuclear wave packet calculations together with high resolution RIXS measurements, we discuss in detail the mode coupling, mode localization and anharmonicity in the studied systems.